P‐88: Efficiency Improvement of Top‐Emission Green Quantum‐Dot Light‐Emitting Diode with Dielectric‐Metal‐Dielectric Cathode. Issue 1 (28th June 2022) - Lin, Bo-Yen; Chen, Chia-Hsun; Lin, Kun-Rong; Lee, Chun-Yu; Chiu, Tien-Lung; Lee, Jiun-Haw
Abstract : In this work, we have demonstrated a top‐emission green quantum dot light‐emitting diode (QLED) with dielectric‐metal‐dielectric (DMD) structure as transparent cathode, which consisted of ytterbium (Yb)‐doped molybdenum oxide (MoO3 )/Yb:Ag/MoO3 . The DMD‐QLED exhibited a reduced operational voltage and higher efficiency by 1.43‐folds enhancement in external quantum efficiency relative to reference QLED due to the improvement of electron injection and transport as well as less exciton quenching.